Portrait of Lecturer Competence in Online Learning During the Covid-19 Pandemic - Herdah Herdah; Sudirman Sudirman; Andi Aras (STAI Hubbulwathan Duri, 2022)
This study aims to find out the process of implementing online learning and lecturer competencies during the Covid-19 pandemic. This study uses a mixed methods approach with an exploratory sequential design. The population in this study amounted to 265 people. The research sample amounted to 160 people consisting of lecturers and students at the Arabic Language Education Study Program, Tarbiyah Faculty of IAIN Parepare. The data analyzed is the result of in-depth interviews and questionnaires. From the results of the study, it can be seen that the pedagogic competence of lecturers plays a very important role in creating effective online learning. This can be seen from the lecturers' efforts in improving the quality of classroom management starting from planning, implementing, and evaluating which have been integrated with learning technology. This study also found that lecturers have pedagogic competence, professional competence, personality competence, and social competence in both categories in carrying out online learning.